The Iowa K-12 Career Guidance Curriculum Guide for Student Development - Iowa State Dept. of Education, Des Moines; Iowa State Dept. of Education, Des Moines ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
This guide was designed to be responsive to societal changes and to help young people learn how to live, learn, and make a living. The first chapter contains an introduction to and overview of the total guide and was written for a broad audience, including parents, school board members, administrators, and teachers. It emphasizes that quality programs of guidance services respond to the needs of all individuals in a comprehensive and developmental way. The second chapter develops a common vocabulary for the implementation or the redirecting of guidance program goals and objectives. The content of the chapter discusses the major program components, career guidance and counseling functions, and the planning process. The third chapter provides examples of a guidance curriculum for grades K-3, 4-6, 7-9, and 10-12. The fourth chapter provides information concerning the various standards, rules, and requirements contained in the Code of Iowa, Standards for Approved Schools, and the certification requirements that are presently in effect and which apply to all Iowa couneslors and school districts. The chapter also provides detailed program guidelines, including evaluative criteria. The final chapter contains a listing of resources that may be of assistance to counselors as they implement or redirect programs of guidance services. (NB)
ERIC Note: Document printed on colored paper.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Guidance; Curriculum Guides; Elementary Secondary Education; Program Implementation; School Counselors; Student Development; Iowa; Guides, General